Understanding Islam in the West - Heba Raouf Ezzat (International Institute of Islamic Thought, 1998)
Gilles Kepel, Allah in the West: Islamic Movements in America and Europe (Stanford, CA Stanford University Press, 1997). 273 pp. Adam LeBor, A Heart Turned East: Among the Muslims of Europe and America (London: Little, Brown and Company, 1997), 322 pp. Understanding Islam and the West is not as easy a task as it might seem. If one attempts to study Muslims living in the West, one is faced by millions of people who are divided among different states, come from different ethnic origins, adopt different schools of thought and understanding within their belief system, and incorporate a realm of perspectives, movements, subcultures, and contradicting positions toward the West. Conversely, if one chooses to study the West in Dar al-Zslum, one is bound to face a past full of conflict and confrontations, a present of intellectual hesitation and unbalanced power relationships, and a future of confusing choices and questions on the prospects of democratidon and the gains/losses of increasing globalization. Hence, scholars choose to focus on one aspect. Recent attempts include studying Islam in relation to the West on a purely philosophical level (e.g., Khuri), the compatibility of Islam and democracy, the future of the process of democratization in the Islamic world (e.g., Esposito and Voll), and studying the response of Muslim intellectuals to the questions and concepts of modernity, (e.g., Cooper and Nettler).' ...